Tingkat Penerimaan Konsumen Terhadap Market Place di Facebook - Nabila Payapo; Sanusi Amir; Heri Abijono (CAHAYA AKTIVA, 2020)
Data from the Ambon City Statistic Agency in 2017 states that as much as 92.37 percent of Ambon City residents live in urban areas. The East Kabar Daily Newspaper in 2019 said every Ambonese citizen must have a handphone. There is an exception, that the use of Facebook is not yet familiar to use for e-commerce, because it still prioritizes direct face-to-face buying with sellers or through classified advertisements in newspapers, and this results in the future level of Ambonese acceptance becoming low towards ecommerce through Facebook, and online marketers have lost the opportunity to transact, so Ambonese people can be left behind compared to other areas in ecommerce through Facebook. The path analysis results concluded that Ease of Use (PEOU) had a significant direct effect on Perceived Usefulness PEOU had a significant indirect effect on Attitude Toward Using (ATU), PEOU PU indirectly had a significant effect on ATU, ATU directly gives a significant on Behavioral Intention Use (BIU), and BIU directly has a significant on Actual System Usage (ASU). With the achievement score analysis of Facebook features, it produces that Facebook features can be further by adding other facilities to attract respondents' attention so they are to open Facebook at least 1 hour per day for e-commerce activities.Keywords: facebook, e-commerce, analysis, pathway, achievement, score